Analisis Komparatif Konsep dan Metode Pendidikan Islam untuk Anak dalam Perspektif Syekh Nawawi Al-Bantani dan Abdullah Nashih 'Ulwan - Kamila Rahma Shalehah; Salsabila Salsabila; Anggi Kurniawan; Syarifah Alawiyah; Abdul Fadhil (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
This research is motivated by the rampant moral decadence that needs attention. Underlining the responsibility of parents and educators in educating children, including the importance of the right method to shape children's faith, morals, knowledge, mentality, and social. Sheikh Nawawi Al Bantani and Abdullah Nashih 'Ulwan were appointed as the main focus because of their influential thoughts in the context of children's education. The purpose of this study is to describe, compare, and analyze the relevance of the thoughts of the two figures regarding children's education in the context of contemporary Islamic education. This study uses a Qualitative Descriptive-Analytical approach with a literature review nature. The data obtained are sourced from primary data as the main reference obtained from a book entitled Tarbiyatul Aulad Fil Islam by Dr. Abdullah Nashih 'Ulwan and the book Tanqih Al-Qaul by Sheikh Nawawi Al-Bantani. While secondary data is obtained from journals, expert books, and previous scientific articles. Descriptive in explaining the arguments and comparison of the two concepts and methods, analysis to describe the contents in depth. In this study it was found that the educational methods proposed by Sheikh Nawawi al-Bantani and Abdullah Nashih have similarities even though the approaches and implementations are different, both discuss Islamic education that prioritizes noble morals which are very relevant considering the contemporary era which is full of moral crises.